Toward Entry-Level Competencies in Cardiovascular and Pulmonary Physical Therapy. Issue 4 (December 2015) - Bartlo, Pamela; Brooks, Gary; Cohen, Meryl
Abstract : Purpose: This article reports on previous efforts to identify entry-level skills for cardiovascular and pulmonary physical therapy (CVP PT), including the most recent surveys of entry-level CVP PT practice. Previous descriptions of entry-level CVP PT skills did not establish competencies, which indicate the minimum level at which a skill should be performed. This information may help guide future efforts to develop these competencies. Methods: Surveys on CVP PT examination and intervention, including 156 and 105 practice behaviors, respectively, were administered to random samples in 2005 and 2008 of all American Physical Therapy Association members regardless of Section affiliation. Respondents indicated whether each behavior was entry level, beyond entry level, or not important. Results: Response rates for the examination and intervention surveys were 7.3% (N = 167) and 4.4% (N = 354) respectively. At least 40% of respondents indicated that 100 items on the examination survey and 89 items on the intervention survey were at entry level. Conclusions: Competencies should be standardized, easily assessed, and identify clear guidelines for achieving success, remediation, or failure. They should be based on a representative description of practice, expert opinion on current practice, and evidence of effective examinations and interventions. Rankings of practice behaviors may contribute to the development of entry-level competencies.